Fingerprinting sengon (Falcatria moluccana) accessions resistant to boktor pest and gall rust disease using microsatellite markers - Ulfah Juniarti Siregar; DEWI RAHMAWATI; APRILIYA DAMAYANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Siregar UJ, Rahmawati D, Damayanti A. 2019. Fingerprinting sengon (Falcatria moluccana) accessions resistant to boktor pest and gall rust disease using microsatellite markers. Biodiversitas 20: 2698-2706. Sengon (Falcataria moluccana Miq.) is a multipurpose fast-growing tree species and widely planted as community forest in Indonesia. According to Indonesian Light Wood Association (ILWA) F. moluccana wood products coming from forest industries in Jawa worth US$ 244.46 million export to China alone. The wood dust also has high potential as source for biomass-based energy in the form of wood-pellet. Monoculture plantation however often suffers from stem borer pest, known as boktor (Xystrocera festiva) and a gall rust disease, caused by fungi Uromycladium falcatarium. This research was aimed to characterize accessions of resistant and susceptible sengon individuals to both gall rust disease as well as stem borer pest using microsatellite markers. Totally 50 accessions of resistant and of resistant to stem borer pest were collected from Sumedang, West Jawa Province, while 88 accessions of resistant and of resistant to gall rust disease were sampled from Kediri, East Jawa Province and Sukabumi, Indonesia. Eight microsatellite markers could amplify most of the accessions used in this study and produce polymorphic fragments. High genetic diversity was detected in all of F. moluccana populations, with He ranged from 0.431 to 0.650. AMOVA showed that most genetic variations come from within populations. A dendrogram based on Nei’s genetic distance (1972) clustered some resistant accessions to either stem borer pest or gall rust disease separately from susceptible ones.